PENERAPAN MODEL GROUP INVESTIGATION PADA MATERI PELESTARIAN SUMBER DAYA ALAM DI INDONESIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD NEGERI PINEUNG - Gusti Handayani (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2021)
The purpose of this study was to determine the application of the Group Investigation learning model to increase the activity of fourth grade students. The method used is classroom action research (CAR) which is carried out in three cycles. The research subjects were 21 graders of SD Negeri Pineung. The data were collected by means of tests, observation sheets, interviews, field notes and documentation. The results showed that the average score in the first cycle was 43 with a percentage of 0%. Furthermore, the acquisition of the average value in the second cycle is 67 with a percentage of 42%. And the acquisition of the average score in the third cycle reached 82 with a percentage of completeness reaching 100%.